Planejamento e competitividade no turismo: estudos sobre as políticas públicas e a governança local de Gramado (RS) - Trindade, Bianca da Silva (My University, 2020)
Planning and management based on tourism governance has been presented as a matter of relevant interest, when seeking to understand the best way to increase the competitiveness of a tourism destination. In this study the main objective was to analyze the influence of public policies and local governance on the competitiveness of Gramado (RS). To achieve the proposed objective, a bibliographical research was carried out, the theory used in relation to the theme of this research was about tourism, planning and management, public policies, tourism governance and competitiveness in tourist destinations. Methodologically the research is qualitative and quantitative and has a descriptive character. For data collection, we used document analysis, questionnaires and semi-structured interviews. The documentary process was based on official tourism documents at national and local level, related to the public management of Gramado (RS), based on its laws, decrees, regiments and statutes, whose purpose was to identify public policies for planning and local tourism management. Information from official documents provided insights into the process of organizing local governance. The application of questionnaires aimed at quantitative analysis was composed of closed questions about the indicators that contribute to a tourist destination becoming competitive, and had as respondents the social actors of local governance responsible for managing the competitiveness of the tourist destination Gramado (RS). The semi-structured interviews, which served as the basis for the qualitative analysis, based on questions that dealt with the planning and management of tourism activity, were also applied with the social actors of local governance, providing complementary information in order to identify the perceptions to be addressed respect for the organizational structure of governance in the current model of destination planning and management. The evidence identified by the present research showed that the governance structure found in Gramado (RS), based on tourism policies at the national, state, regional and local levels, contributes to the development of local and regional tourism activity, since. The performance of the public and private sectors allows the articulation and cooperation regarding the planning and management of the activity, providing the studied tourist destination with a strategic differential, through the offer of higher quality products and a management focused on the competitiveness of the enterprises.
O planejamento e a gestão a partir da governança do turismo tem se apresentado como um assunto de interesse relevante, quando se busca compreender qual a melhor maneira para aumentar a competitividade de uma destinação turística. Neste estudo o objetivo principal foi analisar a influência das políticas públicas e da governança local sobre a competitividade de Gramado (RS). Para alcançar o objetivo proposto realizou-se uma pesquisa bibliográfica, a teoria utilizada em relação ao tema desta pesquisa versou sobre turismo, planejamento e gestão, políticas públicas, governanças de turismo e competitividade em destinações turísticas. Metodologicamente a pesquisa é de natureza qualitativa e quantitativa e, possui caráter descritivo. Para a coleta de dados, utilizou-se a análise documental, aplicação de questionários e realizou-se entrevistas semiestruturadas. O processo documental teve como referência os documentos oficiais de turismo em âmbito nacional e local, relacionados à gestão pública de Gramado (RS), a partir de suas leis, decretos, regimentos e estatutos, cuja finalidade foi de identificar as políticas públicas de planejamento e gestão do turismo local. As informações oriundas dos documentos oficiais trouxeram subsídios de compreensão do processo de organização da governança local. A aplicação dos questionários voltados às análises quantitativas foi composto por questões fechadas sobre os indicadores que contribuem para uma destinação turística se tornar competitiva, e teve como respondentes os atores sociais da governança local responsáveis pela gestão da competitividade do destino turístico Gramado (RS). As entrevistas semiestruturadas as quais serviram de base para a análise qualitativa, a partir de questões que abordaram o planejamento e a gestão da atividade turística, também foram aplicadas com os atores sociais da governança local, fornecendo informações complementares, a fim de identificar as percepções a respeito da estrutura organizacional da governança, no atual modelo de planejamento e gestão do destino. As evidências identificadas pela presente pesquisa permitiram constatar que a estrutura de governança encontrada em Gramado (RS), baseada nas políticas de turismo em âmbito nacional, estadual, regional e local, contribui para o desenvolvimento da atividade turística local e regional, uma vez que, a atuação dos setores público e privado permite a articulação e a cooperação com relação ao planejamento e à gestão da atividade, proporcionando à destinação turística estudada um diferencial estratégico, por meio da oferta de produtos de maior qualidade e uma gestão focada na competitividade dos empreendimentos.
Keywords: Turismo - Gramado (RS); Turismo e planejamento urbano - Gramado (RS); Política pública; Tourism - Gramado (Brazil); Tourism and city planning - Gramado (Brazil); Public policy